Trends of hepatitis B notification rates in Turkey, 1990 to 2012 - (:unkn) unknown (My University, 2013)
Turkey is a country with intermediate endemicity for hepatitis B, and approximately 4% of the population are HBsAg-positive. A number of measures have been implemented to prevent hepatitis B infection. In 1998, hepatitis B antigen was included in the national immunisation programme, and infants have since been vaccinated with three doses. Catch-up strategies, vaccination for high risk groups and screening measures were also adopted. The aim of this study was to evaluate the impact of the prevention and control strategies on hepatitis B notification rates in Turkey in the period from 1990 to 2012, using data from the national surveillance system. Secular trends revealed that rates showed an initial increasing trend, followed by a steady decline from 2005. The most dramatic decline occurred among children younger than 15 years, highlighting the benefits of vaccination and catch-up strategies. However, vaccination cannot fully explain the decrease in this age group. Socioeconomic development, through interrupting the horizontal transmission may also have contributed. After 2005, a steady decline was achieved also among those 15 years and older. The rates in adults were higher, which indicates that stronger prevention measures are needed to target this group, particularly men.